The Role of Local Communities in Managing Human-Elephant Conflict in Sumatra: Challenges and Opportunities for Conservation - Vera Maulinda; Abdullah Abdullah; Safrida Safrida; M. Ali S; Ismul Huda (Jurnal Penelitian Pendidikan IPA, 2025)
Human-elephant conflict (HEC) involving the Sumatran elephant (Elephas maximus sumatranus) remains a significant threat to biodiversity and the livelihoods of rural communities in Aceh Province, Indonesia. This study aims to explore the role of local communities in managing HEC by assessing their level of participation and identifying related challenges and opportunities for conservation. A descriptive quantitative method was applied using a Likert-scale questionnaire distributed to 100 respondents across five villages in Glumpang Tiga and Sakti subdistricts, Pidie Regency. The study assessed three variables: willingness, ability, and opportunity to participate. The results show that overall community participation was in the high category, with a total score of 2.948. Key challenges included limited knowledge, inadequate institutional support, and economic constraints. Meanwhile, the study identified several opportunities such as strong community commitment to conservation, the existence of local customary institutions, and increasing awareness of the importance of elephant protection. These findings highlight that although barriers persist, there is strong potential for enhancing local participation through targeted, community-based strategies. Strengthening collaboration between communities, government, and conservation actors is essential to support sustainable human-elephant coexistence in Sumatra.